Patients with idiopathic recurrent miscarriage have abnormally high TGFß+ blood NK, NKT and T cells in the presence of abnormally low TGFß plasma levels - Zhu, Li; Kuon, Ruben-Jeremias; Morath, Christian; Ekpoom, Naruemol; Daniel, Volker (BMC immunology, 2019)
Previously, we demonstrated up-regulated activated CD4+ and CD8+ T lymphocytes as well as up-regulated cytotoxic NK cells in the blood of patients with idiopathic recurrent miscarriage. In the present study, we tried to identify deficiencies in counter-regulating immune mechanisms of these patients.
Gesehen am 15.07.2019